Association Between Vitamin D and Hyperuricemia Among Adults in the United States - Zhang, Yi-Ying; Qiu, Hong-Bin; Tian, Jin-Wei (Frontiers in Nutrition, 2020)
Background: Serum uric acid can act as a risk factor for cardiovascular disease (CVD) and as antioxidant defense. Vitamin D deficiency can activate parathyroid to induce the release of parathyroid hormone, which was thought to increase serum uric acid level, and low vitamin D status may also be associated with risk of CVD. No known studies have explored the association between serum 25(OH) D, vitamin D intake and HU for the American population. Methods: We extracted 15,723 US adults aged 20–85 years from the National Health and Nutrition Examination Survey (NHANES) in 2007–2014. All dietary intakes were evaluated through 24 hour dietary recalls. Multivariable logistic regression analysis was performed to examine the associations after adjustment for confounders. Results: Compared to the lowest quintile (Q1), for males, adjusted odds ratios (ORs) of HU in Q2 to Q4 of serum 25(OH) D levels were 0.78 (95% CI, 0.65–0.93), 0.97 (0.81–1.16), 0.72 (0.60–0.88); ORs in Q2 to Q5 of total vitamin D intake were 0.83 (0.69–0.98), 0.69 (0.58-0.83), 0.66 (0.55-0.79), 0.59 (0.48-0.71), respectively. In females, OR was 0.80 (0.66-0.97) of serum 25(OH) D for Q3; and ORs in Q5 of total vitamin D intake were 0.80 (0.65-0.98). Conclusions: Our findings indicated the serum 25(OH) D, intakes of dietary vitamin D, supplemental vitamin D and total vitamin D were inversely associated with HU in male. In females, a lower risk of HU with higher serum 25(OH) D, dietary vitamin D and total vitamin D intake was found, but with no association between supplemental vitamin D intake and the risk of HU.